Comparative study of methanol gas sensing performance for SnO2 nanostructures by changing their morphology. (1st June 2020) - Song, Liming; Zhao, Bing; Ju, Xiangnan; Liu, Li; Gong, Yimin; Chen, Wenbin; Lu, Bingliang
Abstract: In this work, the tin oxide material with different morphologies were synthesized by a simple and environmentally friendly hydrothermal method followed by calcination in air. Detail structural, chemical characterization and gas sensing examination of SnO2 nanomaterials with different morphologies have been accomplished. Through a comparative gas sensing research among the as-synthesized SnO2 nanomaterials with different morphologies in our work, the hierarchical SnO2 nanoflowers shows the highest methanol gas sensitivity due to it owns the biggest surface area. The results indicate that the hierarchical SnO2 nanoflowers is the most suitable for the detection of methanol molecule among the as-synthesized SnO2 nanomaterials with different morphologies.